“Las TIC en la evaluación de aprendizajes en el área de matemática” - Chacón Molina, Ericka Cristina (2023)
ICT in the evaluation of learning in the area of mathematics, a study that aimed to apply technological tools to strengthen the evaluation of learning of third grade students in the "Catorce de Julio - JAE" Educational Unit, located in the province of Cotopaxi, Latacunga canton, San Buenaventura parish. This research was designed with an inductive method, under a qualitative approach, because it allows to focus the object of study. The observation technique is used with its observation guide instrument, which provides relevant information on the subject to be investigated. The total population is 35 students in the third year of General Basic Education, parallel "A", so we worked with the entire universe. The technological resource called live worksheet was applied through a formative evaluation. It projects the existing difference between the use of the traditional system to evaluate and doing it through a computer, clearing a background in the psychological conception of the student and eliminating preconceived obstacles of the act of evaluating, while making it a pleasant and positive moment for the student, in addition to this, the resource speeds up the activities of the teaching work, such as the digitalization of documents and the tabulation of data, among others; The impact of this research is of an educational and psychosocial nature due to the influence of the means used to evaluate learning, as well as the individual and collective behavior adopted by those evaluated during the application of these resources.